Motivators and barriers of seasonal influenza vaccination among primary health care physicians in Qatar - Kamran Aziz (21633128) (2024)
Annual influenza vaccination is an effective way to reduce the burden of disease throughout the year. A cross-sectional study was conducted in primary healthcare centres in Qatar to determine vaccination coverage among physicians, motivators, and barriers. The vaccination rate was higher among physicians aged 45 years and above (p-value < 0.005). Most primary care physicians (95 %) strongly agree that being vaccinated reduces the risk of disease spread. The most frequently mentioned barriers were the belief that one could still get influenza after being vaccinated and the fear of side effects (92.6 % and 29.5 %, respectively). Health authorities can implement strategies that take these factors into account to increase immunization coverage. Other Information Published in: Preventive Medicine Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.pmedr.2024.102595